2020
DOI: 10.1080/09650792.2020.1724169
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between research and practice: how teachers use research-based knowledge

Abstract: The article analyses how research-based knowledge is used in practice in an action research project about student dropout. The action research is conducted as research circles with a systematic and organised cooperation between researchers and practitioners, i.e. college teachers. Based on interviews with the teachers, we found that research-based knowledge was used in several ways: as concepts for discussing real-world experiences, as confirmation of the teachers' practical experiences, as a frame for underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
(22 reference statements)
0
5
0
1
Order By: Relevance
“…A college instructor should be able to construct lesson plans, monitor and control classrooms, and teach students in accordance with their aptitude in the ever-changing background of the times. It is possible for colleges and universities to increase college instructors' teaching abilities and set the groundwork for the nurturing of talent in colleges and universities by developing teachers' professional development [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A college instructor should be able to construct lesson plans, monitor and control classrooms, and teach students in accordance with their aptitude in the ever-changing background of the times. It is possible for colleges and universities to increase college instructors' teaching abilities and set the groundwork for the nurturing of talent in colleges and universities by developing teachers' professional development [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Action research can be seen as a way to work with research from this bottom-up perspective, where teachers' questions and issues for improvement are at the center of the processes of engaging in research, but knowledge from quantitative studies and systematic reviews might also be considered (Timperley 2011;Wahlgren and Aarkrog 2020). Such processes are developed over time, and are based on teachers' experiences and contextual knowledge, collaboration, and teacher ownership (cf.…”
Section: Introductionmentioning
confidence: 99%
“…The social-political arrangements [24] for the meeting practice made it possible for the PE teachers to collaborate and develop the activities. Indeed, a previous study confirms the value of researchers and practitioners working together to develop teachers' actions [18]. Finally, some PE teachers expressed that their school principal had decided that PuLH should become an ordinary part of the school day, which is a material-economic arrangement [24] that enables the PE teachers' implementation of PuLH.…”
Section: Become Very Negative and Have Even Started To Put Invalid Ab...mentioning
confidence: 88%
“…The goal was to provide the PE teachers with conditions that enable them to change their practice and address the constraints satisfactorily (i.e., [34,35]). Indeed, previous research has shown the value of researchers and practitioners working together [18,22].…”
Section: Research Circlementioning
confidence: 99%
See 1 more Smart Citation